2016
DOI: 10.1016/j.crci.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity in the oxidative dehydrogenation of ethane over Ni and/or Co molybdate catalysts: Synthesis and characterization

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…Among various choices of reactive catalysts, Ni-based catalyst has been widely used in various catalytic applications, such as stream reforming processes, , water–gas shift reaction, , and biomass gasification . Ni-based catalyst has also been reported as a good catalyst for hydrogenation and dehydrogenation of small alkanes. Recently, this catalyst has been reported as a candidate for the PDH process due to its high reactivity for hydrocarbon reaction, eco-friendliness, and lower cost compared to Pt-based catalysts. , Yan et al experimentally studied PDH reaction on Ni supported by SiO 2 (Ni/SiO 2 ). They found that the reaction rate of propane conversion is very high (about 1 × 10 14 molecule/s at 523 K).…”
Section: Introductionmentioning
confidence: 99%
“…Among various choices of reactive catalysts, Ni-based catalyst has been widely used in various catalytic applications, such as stream reforming processes, , water–gas shift reaction, , and biomass gasification . Ni-based catalyst has also been reported as a good catalyst for hydrogenation and dehydrogenation of small alkanes. Recently, this catalyst has been reported as a candidate for the PDH process due to its high reactivity for hydrocarbon reaction, eco-friendliness, and lower cost compared to Pt-based catalysts. , Yan et al experimentally studied PDH reaction on Ni supported by SiO 2 (Ni/SiO 2 ). They found that the reaction rate of propane conversion is very high (about 1 × 10 14 molecule/s at 523 K).…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene is one of the most produced and essential chemical products in the world [1][2][3]. Oxydehydrogenation of C 2 H 6 with CO 2 to C 2 H 4 provides new ideas for pressing issues (energy conservation and emission reduction, green chemical industry, sustainable development) [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A lo largo de los últimos años, un gran número de catalizadores basados en metales de transición se han preparado de los cuales los catalizadores basados en níquel han reportado alcanzar buenos niveles de conversión de etano, sin embargo, la selectividad es todavía una tarea difícil de mejorar. La incorporación de promotores en la red de NiO tales como Ta, Nb, Ce, Co, W y Al aumentó el rendimiento de los catalizadores basados en NiO [4][5][6][7][8][9] . Heracleous y col. 6 , reportaron que la adición de promotores con valencia mayor que Ni 2+ tuvo un efecto positivo en el logro de buenas selectividades ya que eran capaces de disminuir los defectos catiónicos, y por lo tanto, las especies de oxígeno no selectivos que conllevan a la sobreoxidación de la olefina.…”
Section: Introductionunclassified
“…Un método de evaporación Rev Soc Quím Perú. 82 (4) 2016 simple pero controlada se realizó con el fin de favorecer la integración de fases para formar una solución mixta.…”
Section: Introductionunclassified